PENGATURAN MENGENAI PERLINDUNGAN HUKUM BAGI KREDITUR YANG TERLAMBAT MENDAFTARKAN PIUTANGNYA BAGI PKPU DI INDONESIA: Provisions Regarding Legal Protection for Creditors who are Late in Registering their Claims in PKPU Proceedings in Indonesia - Intan Naila Fadhillah; Sri Bakti Yunari (Faculty of Law, Universitas Trisakti, 2026)
In the Indonesian economic system, there is a Debt Payment Obligation Deferral (PKPU) mechanism to prevent a company from becoming insolvent with regard to its assets. The PKPU mechanism involves a settlement agreement proposed by the debtor, which must be approved by the creditors. Once approved by the court, the result is a homologated settlement agreement. The problem formulation is how to regulate creditors who are late in registering their receivables in the PKPU process in Indonesia. The research method used is descriptive and normative, using secondary data supported by interviews. The results of the discussion and conclusion show that Law 37 of 2004 regulates late registration, but only for a period of two days of delay in Article 278 paragraph (3). Creditors who experience a delay of more than two days can file an appeal, which will then be assessed by the court based on the principles of justice and legal certainty. Although Law No. 37 of 2004 does not explicitly regulate creditors who are late beyond this period.